Influence of drying methods on heavy metal composition and microbial load of plantain chips - Adenitan, A.A.; Awoyale, W.; Akinwande, B.; Maziya-Dixon, Busie (Informa UK Limited, 2022)
Mature unripe plantain is usually processed into chips using the traditional sun-drying method without considering consumer safety. Thus, there is a need to assess the influence of solar tent and open sun drying on the heavy metal composition and microbial load of plantain chips. Thirty samples of dried plantain chips were collected randomly from 10 processing centers in Akure South and Idanre Local Government Areas of Ondo State, Nigeria. In addition, four popularly consumed plantain varieties (agbagba, bobby tannap, mbi egome, and pita 23) were processed to chips and dried using open sun and solar tent drying. The samples were analyzed for heavy metal compositions using an Inductively Coupled Plasma- Optical Emission Spectrometer (ICP-OES) and microbial loads using the serial dilution method. The heavy metal content of the dried plantain chips was in the range of 0.01–0.08 mg/kg for Cd, 0.01–0.07 mg/kg for Co, and 0.05–0.50 mg/kg for Pb. Seven fungi (Penicillium spp., Rhizopus spp., Aspergillus flavus, Aspergillus Niger, Aspergillus tamarii, Fusarium verticillioides, and Monilla spp.) of health importance were isolated. The drying methods had a significant effect on the Cd (p < 0.01), Co (p < 0.001), and Pb (p < 0.01) contents of the plantain chips, but with no significant effect (p > 0.05) on the bacterial, fungi, and total coliform counts. Since the heavy metal content and microbial loads were higher in the surveyed and open sun-dried samples, the solar tent-dryer may be more reliable in producing less contaminated plantain chips than the open sun drying methods.